Seasonal Variations of Soil Thermal Conductivity at the InSight Landing Site. Issue 7 (3rd April 2023) - Grott, M.; Piqueux, S.; Spohn, T.; Knollenberg, J.; Krause, C.; Marteau, E.; Hudson, T. L.; Forget, F.; Lange, L.; Müller, N.; Golombek, M.; Nagihara, S.; et al.
Abstract: The heat flow and physical properties package measured soil thermal conductivity at the landing site in the 0.03–0.37 m depth range. Six measurements spanning solar longitudes from 8.0° to 210.0° were made and atmospheric pressure at the site was simultaneously measured using InSight's Pressure Sensor. We find that soil thermal conductivity strongly correlates with atmospheric pressure. This trend is compatible with predictions of the pressure dependence of thermal conductivity for unconsolidated soils under martian atmospheric conditions, indicating that heat transport through the pore filling gas is a major contributor to the total heat transport. Therefore, any cementation or induration of the soil sampled by the experiments must be minimal and soil surrounding the mole at depths below the duricrust is likely unconsolidated. Thermal conductivity data presented here are the first direct evidence that the atmosphere interacts with the top most meter of material on Mars. Plain Language Summary: A soil's ability to transport heat is a fundamental parameter that holds information on quantities like soil bulk porosity, composition, grain size, and the state of cementation or induration. In the soil, heat is transported through grain‐to‐grain contacts as well as through the pore filling CO2 gas. The heat flow and physical properties package (HP 3 ) of the InSight Mars mission measured soil thermal conductivity at the landing site repeatedly over the course of a martian year. As atmospheric pressure changes between seasons due to the redistribution of CO2 across the planet, we found that soil thermal conductivity also changes. Thermal conductivity increased for increased atmospheric pressure, a behavior typical for unconsolidated material. This implies that the amount of cement or induration of the sampled soil must be minimal. Key Points: We measured thermal conductivity of the martian soil and found that its conductivity strongly correlates with atmospheric pressure We conclude that heat conduction through the pore‐filling gas is significant and that cementation of the soil must be minimal Our data show that the atmosphere directly interacts with the top most meter of material on Mars